Pengaruh Penggunaan Soil Stabilization Terhadap Sifat Fisik Mortar Dengan Agregat Halus Berkadar Lumpur Tinggi - Rahman, Arif; Ismeddiyanto, Ismeddiyanto; Suryanita, Reni (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2018)
This study examined the physical properties of mortar mixed from fine aggregate containing high percentage of mud and soil stabilization. According SNI S-04-1998-f regulations fine aggregates for concrete should not be more 5% mud. Soil stabilization as additive material in the mortar mixtures will increase the quality of mortar.. The percentage of mud in the study was 0%, 5%, 10%, 15%, 20% and 23%. Soil stabilization of 1% as additional material of the mortar’s mud weight. The tested physical properties of the study object consist of its unit weight, sorptivity, porosity amd compressive strength. Study object was treated by submerging in normal water in 28 days. The compressive strength of mortar with high mud content and added soil stabilization is higher 2.82%, 4.74%, 8.16%, 13.94% and 16.03% compared to mortar with high mud content without soil stabilization at 5%, 10%, 15%, 20% and 23% mud content variation.The porosity of mortar with high mud content and added soil stabilization is higher22,21% compared to mortar with high mud content without soil stabilization. Sorptivy test results added soil stabilization value 0,1 mm/min0,5- 0,2 mm/min0,5 which means mortar is good. The unit weight mortar with high mud level and added soil stabilization is higher by average unit weight 2,31 gr/cm3 compared to mortar with high mud content without soil stabilization. Based on the overall study, it’s concluded that the overall strength of mortar with high mud content and added soil stabilization is higher than mortar with high mud content without added soil stabilization.Keywords : Mud, Soil Stabilization, Mortar.